Hungary : Report on the Observance of Standards and Codes-Data Module-Update. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents an update to the Report on the Observance of Standards and Codes on Data Module for Hungary. Hungary continues to observe the specifications of the Special Data Dissemination Standards for the coverage, periodicity, and timeliness of all data categories, including the detailed template on international reserves and foreign currency liquidity, and for the dissemination of advance release calendars. The metadata and summary methodologies underlying the economic statistics are regularly updated on the IMF's Dissemination Standards Bulletin Board.